Role of Organization Identification in Employee Retention : Examining Mediating Effects in the Private Sector - Farrossabilla, Allya Rizky Okza; Maksum, Ikhsan (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Purpose: This study analyzes how job conditions and training development impact employee retention, with organizational identification as a mediating factor. Methodology: A quantitive approach was employed, utilizing a survey of 112 respondents from PT Panasonic Industrial Devices Batam. Data were analyzed using SEM-PLS. Findings: Job conditions and training development significantly influence employee retention. Results: Organizational identification does not significantly mediate these relationships. Novelty: Highlights the limited mediating role of organizational identification in a manufacturing context. Originality: Provides insights for HR strategies beyond traditional employee engagement models. Conclusion: Organizational identification is not a critical mediator, suggesting that direct HR interventions on job conditions and training yield better retention outcomes. Type of Paper: Empirical research.